Ulipristal acetate (UPA) for fibroids–IVF outcomes following treatment with UPA after IVF failure: series of 2 case reports - Kale, Ashish R (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine fibroids (also known as leiomyomas or myomas) are the most common form of benign uterine tumors. Fibroids are present in 5-10% of infertile patients, and may be the sole cause of infertility in 1-2.4%. The removal of fibroids by hysteroscopy and laparoscopy has now become the standard of care depending upon the size, number and location of fibroids in an infertile woman. Off lately, there is growing evidence of the crucial role of progesterone pathways in the pathophysiology of uterine fibroids due to the use of selective progesterone receptor modulators (SPRMs) such as ulipristal acetate (UPA). Here, we report a case series of 2 women, with fibroids, who were put on UPA prior to IVF. These women had at least one previous IVF failure. The pre and post UPA fibroid characteristics were compared to see the effect of the drug. IVF was done post 3 month UPA therapy. Both the women showed a drastic reduction in the fibroid size, increased distance from endometrial cavity, and successful post UPA IVF cycles. Safety of the drug has been proven in few recent trials, but the role of UPA in infertile women with fibroids, who have had previous IVF failure, has opened new horizons in this field.